MOTIVASI KERJA DENGAN TINGKAT KEDISIPLINAN PERAWAT DI RUANG RAWAT INAP RSUD. OTANAHA KOTA GORONTALO - Sabirin B. Syukur; Rini Asnawati; Tri Gunawan Sidiki (Zaitun (Jurnal Ilmu Kesehatan), 2019)
Discipline is the most important operative function of human resource management. The factors affecting work discipline are motivation; work motivation is very important in efforts to uphold and improve discipline and have the responsibility to provide optimal and quality nursing services. The purpose of this research was to determine the correlation of work motivation with the level of discipline of nurses in the inpatient room of RSUD Otanaha, Gorontalo city. The design uses quantitative descriptive with cross sectional study approach. The population in this research was 32 nurses by sampling using total sampling so that the number of samples was 32 respondents. The statistical test uses Chi square. With a p value of 0.012 smaller than α <0.05, Ho is rejected and Ha is accepted. It can be concluded that there is a significant correlation between Work Motivation and the Discipline Level of Nurses in the Inpatient Room of RSUD Otanaha, Gorontalo city.